PENGUATAN KETERAMPILAN ANDRAGOGI PADA SATUAN PENDIDIKAN NON-FORMAL (SPNF) SEJENIS SANGGAR KEGIATAN BELAJAR (SKB) KABUPATEN PULANG PISAU - Ni Nyoman Astrini Utami; Merry Bendelina Asalaka; Ratih Sulistyowati; Putra Andino Nugrahhu; Octa Maria Sihombing; Dwi Sartica; Amos Jaya Adie Sitinjak; Frenky Albert Timotius (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2024)
Satuan Pendidikan Non-Formal (SPNF) Sejenis Sanggar Kegiatan Belajar (SKB) Kabupaten Pulang Pisau provides equality education programs for people who still need to complete their education successfully. An equal education program is essential for people whose education has stopped. The ages of people who have stopped attending school vary widely, from young to adults. The problem in the SPNF Sejenis SKB Kabupaten Pulang Pisau is the difficulty of conveying material to adult students. The knowledge and skills of tutors in teaching, especially adults, are essential. Based on this, it is necessary to carry out training to strengthen andragogy competencies for learning teachers. After strengthening and empowering, tutors are expected to be able to understand adult teaching, find adult learning strategies to be creative in teaching, and carry out teaching using the strategies that have been found. Based on the evaluation of activities that have been carried out, training to strengthen the andragogy competencies of learning teachers has had a positive impact. Teachers learn based on a theoretical understanding of adult teaching and can creatively make teaching materials and deliver material.